Quantification of the Influence of Deep Basin Effects on Structural Collapse Using SCEC CyberShake Earthquake Ground Motion Simulations. Issue 4 (November 2019) - Bijelić, Nenad; Lin, Ting; Deierlein, Gregory G.
This paper examines the effects of earthquake ground motions in deep sedimentary basins on structural collapse risk using physics-based earthquake simulations of the Los Angeles basin developed through the Southern California Earthquake Center's CyberShake project. Distinctive waveform characteristics of deep basin seismograms are used to classify the ground motions into several archetype groups, and the damaging influence of the basin effects are evaluated by comparing nonlinear structural responses under spectrum and significant duration equivalent basin and nonbasin ground motions. The deep basin ground motions are observed to have longer period-dependent durations and larger sustained spectral intensities than nonbasin motions for vibration periods longer than about 1.5 s, which can increase structural collapse risk by up to 20% in ground motions with otherwise comparable peak spectral accelerations and significant durations. Two new metrics are proposed to quantify period-dependent duration effects that are not otherwise captured by conventional ground motion intensity measures. The proposed sustained amplitude response spectra and significant duration spectra show promise for characterizing the damaging effects of long duration features of basin ground motions on buildings and other structures.